Role of Multi-Disciplinary Team Clinic in the Management of Orthognathic Patients A Seven Years Review of Orthognathic Surgery - Bashar A. Tawfeeq; Rawaa Y. Al-Rawee; Younis M. Saeed; Dina A. Al-Khashab; Mahmood Kh. Ahmed (University of Mosul, College of Dentistry, 2020)
Aims: to evaluate the need for and benefits of Multi-Disciplinary Team (MDT) clinic in treating orthognathic patients. Materials and Methods: a total number of 272 patients were examined in 2 centers in Mosul. The sample divided into 2 groups, first group diagnosed from Feb 2004 till March 2009 without MDT clinic, while second group diagnosed from April 2009 till July 2011 in MDT clinic, and evaluated for their needs and wants to correct functional and esthetic problems, a criteria were applied to all of them to manage the real need for the surgical work. Results: from total patients seeking treatment, first group were 116 patients, 54 patients (46.5%) operated, while the second group were 156 patients, 33 patients (21.1%) operated. Conclusions: need for surgical correction of facial and gnathic deformities is a three handed subject: patient's real complaint, team work decision and medical staff education.